IMPLEMENTASI METODE PEMBELAJARAN KONTEKSTUAL/CTL BERBASIS PERMAINAN EDUKATIF TERHADAP MINAT BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Evi Novita Sari; Muh. Yazid; Rifaatul Mahmudah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low interest of elementary school students in learning mathematics, which is often perceived as difficult and monotonous. Conventional teaching methods tend to make students passive and less motivated. Therefore, this study aimed to examine the effect of implementing the Contextual Teaching and Learning (CTL) method based on educational games on students’ interest in learning mathematics. This research employed a quantitative approach with a quasi-experimental one-group pretest-posttest design. The population was 24 third-grade students at SD Negeri 1 Dane Rase, Lombok Timur. Data were collected using questionnaires and documentation, and analyzed using validity, reliability, normality, linearity, and hypothesis tests with SPSS 25.0. The findings showed that the implementation of CTL-based educational games significantly increased students’ interest in learning mathematics, as indicated by the improvement in post-test results compared to pre-test. This suggests that combining CTL with educational games creates a meaningful, enjoyable, and engaging learning experience for students.